2021
DOI: 10.1080/23335432.2021.1916405
|View full text |Cite
|
Sign up to set email alerts
|

The ulnar collateral ligament loading paradox between in-vitro and in-vivo studies on baseball pitching (narrative review)

Abstract: Ulnar collateral ligament (UCL) weakening or tears occur in 16% of professional baseball pitchers. To prevent players from sustaining a UCL injury, it is important to understand the relationship between the UCL properties and elbow stabilizers with the load on the UCL during pitching. Invitro studies showed that the ultimate external valgus torque of 34 Nm would rupture the UCL, which is in apparent conflict with the reported peak valgus torques in pitching (40-120 Nm). Assuming both observations are correct, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The in-vitro studies in combination with the results of our study may indicate that the UCL might not resist the entire valgus torque by itself, but that the forearm flexor pronator muscles are able to counteract the valgus torque at least partly during baseball pitching as well. Elbow flexor and extensor muscles, together with the joint articulation, could also indirectly affect the mechanical resistance of the external valgus torque at the elbow during pitching (Van Trigt et al, 2021). In-vitro cadaver studies and forward dynamic model studies showed that the biceps and triceps are important in stabilizing the elbow joint (Morrey et al, 1991;Seiber et al, 2009;Rahman et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The in-vitro studies in combination with the results of our study may indicate that the UCL might not resist the entire valgus torque by itself, but that the forearm flexor pronator muscles are able to counteract the valgus torque at least partly during baseball pitching as well. Elbow flexor and extensor muscles, together with the joint articulation, could also indirectly affect the mechanical resistance of the external valgus torque at the elbow during pitching (Van Trigt et al, 2021). In-vitro cadaver studies and forward dynamic model studies showed that the biceps and triceps are important in stabilizing the elbow joint (Morrey et al, 1991;Seiber et al, 2009;Rahman et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Elbow flexor and extensor muscles, together with the joint articulation, could also indirectly affect the mechanical resistance of the external valgus torque at the elbow during pitching (Van Trigt et al, 2021 ). In-vitro cadaver studies and forward dynamic model studies showed that the biceps and triceps are important in stabilizing the elbow joint (Morrey et al, 1991 ; Seiber et al, 2009 ; Rahman et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations